2023
DOI: 10.1021/acs.est.3c00267
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation Prediction of the Partitioning Constants (KH, Kiw, Kia) of 82 Legacy and Emerging Organic Contaminants at the Water–Air Interface

Abstract: The tendency of organic contaminants (OCs) to partition between different phases is a key set of properties that underlie their human and ecological health impacts and the success of remediation efforts. A significant challenge associated with these efforts is the need for accurate partitioning data for an ever-expanding list of OCs and breakdown products. All-atom molecular dynamics (MD) simulations have the potential to help generate these data, but existing studies have applied these techniques only to a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 136 publications
1
9
0
Order By: Relevance
“…Other approaches to predicting the partitioning of organics to the air-water interface have used polyparameter free energy relationships, 18 the use of commercial soware packages, 25 and molecular dynamics simulations. 14 The report by Lemay et al 14 gives three compounds which are also determined here (pyrene, uoranthene and bisphenol A); that of Goss 27 has only one (naphthalene). The different choice of standard states in these earlier works makes a direct comparison with our predictions and measurements not straightforward.…”
Section: Partitioning To the Water-air Interfacementioning
confidence: 66%
See 1 more Smart Citation
“…Other approaches to predicting the partitioning of organics to the air-water interface have used polyparameter free energy relationships, 18 the use of commercial soware packages, 25 and molecular dynamics simulations. 14 The report by Lemay et al 14 gives three compounds which are also determined here (pyrene, uoranthene and bisphenol A); that of Goss 27 has only one (naphthalene). The different choice of standard states in these earlier works makes a direct comparison with our predictions and measurements not straightforward.…”
Section: Partitioning To the Water-air Interfacementioning
confidence: 66%
“…A very recent study using molecular dynamics simulations has reported a systematic approach to the air–water interfacial partitioning. 14 Nevertheless, it is clear that there remains a clear need for experimental measurements of the water surface partitioning thermodynamics over a range of organic compounds, especially when this surface is modified by organic coating.…”
Section: Introductionmentioning
confidence: 99%
“…MD simulations have also been used to study photosynthesis and the behavior of pollutants in gas, solid, and liquid interfaces , and model the fate and transport of pollutants and compounds, , among other applications. The behavior of pollutants in gas, solid, and liquid interfaces, such as predicting their Henry’s law constant and interfacial adsorption coefficients, has also been explored using MD. , …”
Section: Computational Chemistry Methodsmentioning
confidence: 99%
“…We note that MD simulation predictions are well-known to be sensitive to the choice of interatomic potential models. The SPC/E model was selected as it provides one of the most accurate representations of the properties of liquid water, including surface tension, static and dynamic dielectric properties, hydrogen-bond structure, and self-diffusion coefficient. The OPLS-AA model has been extensively tested against the structural and energetics properties of organic compounds in liquid water and at the water–air interface. Our recent results obtained using a variety of organic compounds show that the combination of the SPC/E and OPLS-AA models reasonably predicts the adsorption of organic compounds from liquid water to the water–air interface …”
Section: Methodsmentioning
confidence: 99%
“…69−71 Our recent results obtained using a variety of organic compounds show that the combination of the SPC/E and OPLS-AA models reasonably predicts the adsorption of organic compounds from liquid water to the water−air interface. 72 Converting Organic Bulk Concentration to Size-Dependent Particle Organic−Water Mass Fraction. A significant challenge in comparing our simulation predictions with published experimental results is that experimental studies generally report the organic concentration in bulk solution (C b ) as a key variable.…”
Section: ■ Introductionmentioning
confidence: 99%